2019
DOI: 10.1002/path.5240
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection induces endoplasmic reticulum stress and apoptosis in human fetal liver stem cells

Abstract: The cellular mechanisms by which hepatitis C virus (HCV) replication might mediate cytopathic effects are controversial and not entirely clear. In this study, we found that blood-borne HCV (bbHCV) infection could lead to endoplasmic reticulum (ER)-stress and mitochondria-related/caspase-dependent apoptosis at the early stages of infection based on use of the highly efficient bbHCV cell culture model established previously. Sections of bbHCV-infected human fetal liver stem cells (hFLSCs) revealed convolution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…On the other hand, Bcl-xL may also be co-responsible for HCV-induced oncogenesis. Research by Guo et al [ 57 ] on human fetal liver stem cells (hFLSCs) infected with HCV has revealed nuclear factor-ĸB (NF-ĸB)-dependent mechanisms that counteract HCV-induced apoptosis at the late stage of infection. One of the cell survival-promoting events was the upregulation of intracellular Bcl-xL [ 57 ].…”
Section: The Role Of Bcl-xl In Hcv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Bcl-xL may also be co-responsible for HCV-induced oncogenesis. Research by Guo et al [ 57 ] on human fetal liver stem cells (hFLSCs) infected with HCV has revealed nuclear factor-ĸB (NF-ĸB)-dependent mechanisms that counteract HCV-induced apoptosis at the late stage of infection. One of the cell survival-promoting events was the upregulation of intracellular Bcl-xL [ 57 ].…”
Section: The Role Of Bcl-xl In Hcv Infectionmentioning
confidence: 99%
“…Research by Guo et al [ 57 ] on human fetal liver stem cells (hFLSCs) infected with HCV has revealed nuclear factor-ĸB (NF-ĸB)-dependent mechanisms that counteract HCV-induced apoptosis at the late stage of infection. One of the cell survival-promoting events was the upregulation of intracellular Bcl-xL [ 57 ]. Meanwhile, previous studies had found the overexpression of Bcl-xL in HCCs and suggested the contribution of its anti-apoptotic activity to HCC survival under various stress conditions, and to hepatocellular carcinoma development [ 58 , 59 ].…”
Section: The Role Of Bcl-xl In Hcv Infectionmentioning
confidence: 99%
“…Apoptosis is an autonomous type of PCD (9). EV71, hepatitis B and C and other viruses induce apoptosis (7,37,38). Viruses tend to use host cells to induce apoptosis of tissue or immune cells to infect the body (39).…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, but some viruses can also trigger cells to produce Bcl-2. Hepatitis C virus and human T-cell leukemia virus (HTLV) both induce Bcl-XL expression, and HTLV also induces Bcl-2 expression by involving the activation of NFκB [ 34 , 35 , 36 ]. In line with this, we observed increased activation of Bcl-2 in BVDV-infected cells, suggesting that it is involved in the observed induction of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%